Thecentury of globalizationpoint of the view “Ideas of a united Turkestan” in media - Akynbekova А.Б.; Tulpar Ж.; Bakenova Р.Ш.; Auyesbay К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
At the beginning of the twentieth century, in the context of the transformation of political systems, the idea of independence and independence of the Turkic-speaking states gained new impetus thanks to the active work of the Kazakh intelligentsia; In the 21st century, a similar situation arose – with new challenges and threats. Purpose: to study the specifics of the formation and development of the idea of a “united Turkestan” in the media of Turkic-speaking countries and in a number of European states by considering the problem of protecting the interests of national minorities during the period of Soviet rule in the Central Asian region. The main methods were the historical method, with the help of which the features of the activities of national liberation movements in Kazakhstan at the beginning of the twentieth century were examined, and the system analysis method, which was used to study the factors influencing the creation of the information image of “united Turkestan” in the press. The results of this work can be used as a practical basis for future scientific research and to improve the strategy for uniting Turkic-speaking states in various areas of cooperation.